Pengaruh Perencanaan Produksi Dan Kualitas Produk Terhadap Kinerja Operasional Yang Dimoderasi Oleh Standar Operasional Prosedur (SOP) Pada PT. Tritunggal Sinarjaya - Ari Soeti Yani; Indri Apriyani Daka (Fakultas Ekonomi dan Bisnis, 2022)
This study aims to analyze and prove the effect of production planning and product quality on operational performance moderated by standard operating procedures (SOP). The types of data used in this study are primary data originating from employees of PT. Tritunggal Sinarjaya with a total of 145 respondents. Sampling of this research sampling technique is Random Sampling. This study analyzes the relationship between the effect of production planning and product quality on operational performance moderated by standard operating procedures (SOP). This study uses data analysis method Partial Least Square (PLS). The results showed that production planning had a significant effect on operational performance. Product quality has no significant effect on operational performance. Standard operating procedures (SOP) have a significant effect on operational performance. Production planning has no significant effect on operational performance which is moderated by standard operating procedures (SOP). And product quality has no significant effect on operational performance which is moderated by standard operating procedures (SOP). Keywords: Production Planning, Product Quality,Operational Performance, Standard Operating Procedures (SOP)